THE EFFECTIVENESS OF PREMARITAL HEALTH COUNSELING ON INTEREST IN DELAYING HIGH-RISK PREGNANCY AMONG PROSPECTIVE REPRODUCTIVE-AGE COUPLES UNDER 20 YEARS OLD AT KEDABURAPAT PUBLIC HEALTH CENTER, MERANTI ISLANDS REGENCY - Iis Susianti; Komaria Susanti (Academic Solution Publisher, 2026)
Pregnancy under 20 years is a high-risk condition because adolescents are not yet biologically, psychologically, and socioeconomically mature. This study examined the effectiveness of premarital health counseling in increasing interest in delaying high-risk pregnancy among prospective couples of childbearing age under 20 years at Kedaburapat Public Health Center, Meranti Islands Regency. A quantitative quasi-experimental design with a one-group pretest–posttest approach was used. The population comprised 40 women of childbearing age under 20 years, and 11 participants were selected through purposive sampling. Data were collected using a questionnaire and analyzed using univariate and bivariate analysis with the Wilcoxon Signed Rank Test. Before counseling, 63.6% of respondents had high interest and 36.4% had low interest. After counseling, all respondents showed high interest. The mean score increased from 24.18 to 41.45, with p = 0.003. Premarital health counseling was effective in increasing interest in delaying high-risk pregnancy.